2021
DOI: 10.3390/w13040470
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons in Sediments from Typical Algae, Macrophyte Lake Bay and Adjoining River of Taihu Lake, China: Distribution, Sources, and Risk Assessment

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental pollutants in sediments and pose a serious risk for freshwater ecosystems. In this study, sediment samples from 24 sites were collected from the cyanobacterial bloom-occurring, macrophyte-growing lake bay and adjoining river of Taihu Lake. Here, the concentration levels, sources, and risk assessment of 16 priority PAHs in the surface sediments from typical algae, macrophyte lake bay and adjoining river of Taihu Lake, were investigated, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Whether the concentration of PAHs in the Taihu Lake Basin exceeded the standard and whether it posed a health threat to the surrounding population had received widespread attention 16 18 . Since 2000, the concentration of PAHs in the sediments of the Taihu Lake Basin had ranged between 698.00 and 962.00 ng g −1 , after 209.00–3842.00 ng g −1 in 2010, and gradually changed to 4900.00–16,800.00 ng g −1 in 2021 19 21 , showing a continuous upward trend. It is imminent to study the concentration, source and carcinogenic risk of polycyclic aromatic hydrocarbons in the sediments of Taihu Lake in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the concentration of PAHs in the Taihu Lake Basin exceeded the standard and whether it posed a health threat to the surrounding population had received widespread attention 16 18 . Since 2000, the concentration of PAHs in the sediments of the Taihu Lake Basin had ranged between 698.00 and 962.00 ng g −1 , after 209.00–3842.00 ng g −1 in 2010, and gradually changed to 4900.00–16,800.00 ng g −1 in 2021 19 21 , showing a continuous upward trend. It is imminent to study the concentration, source and carcinogenic risk of polycyclic aromatic hydrocarbons in the sediments of Taihu Lake in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, PAHs have been the subject of environmental monitoring research for catchments worldwide. Numerous studies have employed water and sediment as important matrices for evaluating PAHs contamination in rivers [17][18][19], lakes [20,21], dams [22] as well as seas [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…[6]. PAHs exhibit semi-volatility, long-term persistence and bioaccumulation of persistent organic pollutants and widely occur in a variety of environmental media [7][8]. Research has indicated that the environmental behavior and bioavailability of PAHs are strongly affected by BC [9].…”
Section: Introductionmentioning
confidence: 99%